Respuesta :
Answer:
The answer is given below
Step-by-step explanation:
In triangle EFG, let a = EG, A = ∠f, b= 1.3 in, B = ∠G, c = 2.4 in C = ∠E = 48°
Using cosine rule:
[tex]c^2=a^2+b^2-2ab*cos(C)\\a^2-2ab*cos(C)=c^2-b^2\\Substituting:\\a^2-2a(1.3)cos(48)=2.4^2-1.3^2\\a^2-1.74a=4.07\\a^2-1.74a-4.07=0\\a=3\ or\ -1.34\\a=EG=3\ inches[/tex]
EG = 3 inches
Using sine rule,
[tex]\frac{b}{sin(B)} =\frac{c}{sin(C)}\\ Substituting:\\\frac{1.3}{sin(B)} =\frac{2.4}{sin(48)}\\sin(B)=\frac{sin(48)*1.3}{2.4}=0.4025\\ B=sin^{-1}(0.4025)=23.7^0[/tex]
∠G = B = 23.7°
Given ΔXYZ ≅ ΔEGF,
Therefore: ZX = EF = 1.3 inches, m∠X = m∠G =23.7 °, m∠Z = m∠F = 107°
ZY = FG = 2.4
Answer:
ZX = 1.3 in.
EG = 3 in.
m∠X = 48°
m∠G = 25°
Step-by-step explanation:
ΔXYZ ≅ ΔEGF
107 + 48 = 155
m∠G = 180 - 155 = 25